2006
DOI: 10.1096/fj.05-5543fje
|View full text |Cite
|
Sign up to set email alerts
|

A negative feedback loop of transcription factors that controls stem cell pluripotency and self‐renewal

Abstract: Embryonic stem (ES) cells possess the ability to renew themselves while maintaining the capacity to differentiate into virtually all cell types of the body. Current evidence suggests that ES cells maintain their pluripotent state by expressing a battery of transcription factors including Oct4 and Nanog. However, little is known about how ES cells maintain the expression of these pluripotent factors in ES cells. Here we present evidence that Oct4, Nanog, and FoxD3 form a negative feedback loop to maintain their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
176
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(190 citation statements)
references
References 23 publications
11
176
0
3
Order By: Relevance
“…P19 cells and F9 cells were cultured in Dulbecco's modified Eagle's medium (Invitrogen) supplemented with 15% fetal bovine serum (Hyclone, UT) and antibiotics (penicillin and streptomycin, 100 g/ml) (3,10). Mouse ES cells (CGR8 ES) were cultured on 0.1% gelatincoated substrates and cultured in Glasgow minimum essential medium (Sigma) supplemented with 20% fetal bovine serum (Invitrogen), 100 mM nonessential amino acids (Invitrogen), 0.55 mM mercaptoethanol (Sigma), 2 mM L-glutamine (Invitrogen), and 1,000 units/ml human recombinant LIF (Chemicon) as described (3,5,6,10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P19 cells and F9 cells were cultured in Dulbecco's modified Eagle's medium (Invitrogen) supplemented with 15% fetal bovine serum (Hyclone, UT) and antibiotics (penicillin and streptomycin, 100 g/ml) (3,10). Mouse ES cells (CGR8 ES) were cultured on 0.1% gelatincoated substrates and cultured in Glasgow minimum essential medium (Sigma) supplemented with 20% fetal bovine serum (Invitrogen), 100 mM nonessential amino acids (Invitrogen), 0.55 mM mercaptoethanol (Sigma), 2 mM L-glutamine (Invitrogen), and 1,000 units/ml human recombinant LIF (Chemicon) as described (3,5,6,10).…”
Section: Methodsmentioning
confidence: 99%
“…The pluripotency of mouse ES cells appears to be governed by a network of transcription factors including Oct4, Sox2, FoxD3, and Nanog (1,(3)(4)(5)(6). Although volumes of data have been generated through large scale biological tools such as microarrays and proteomics about these core regulators of stem cell pluripotency (4,(7)(8)(9), little is known about the molecular mechanisms that govern their mechanism of action.…”
mentioning
confidence: 99%
“…As shown in Fig. 3C, the luciferase activities driven by 286-mut-1, 286-mut-2, 286-mut-3, and 286-mut-4 mutant promoter sequences were no longer responsive to Nanog (lower portion, lanes [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], whereas Rexp286 was responsive to Nanog in a dose-dependent fashion (lanes 1-4). , lanes 1, 5, 9, 13, and 17; 0.25 g, lanes 2, 6, 10, 14, and 18; 0.5 g, lanes 3, 7, 11, 15, and 19; and 0.75 g, lanes 4, 8, 12, 16, and 20) into P19 cells.…”
Section: Regulation Ofmentioning
confidence: 99%
“…Interestingly, Nanog is regulated by an adjacent pair of highly conserved Octamer-and Sox-binding sites through an interaction between Oct-3/4 and Sox2 (13). Our recent work has demonstrated that transcription factors Oct-3/4, Nanog, Sox2, and FoxD3 anchor a negative feedback loop to maintain the expression of pluripotent factors at a steady state (14). In this report, we present evidence that Rex-1 is regulated by Nanog, Oct-3/4, and Sox2 at the transcription level.…”
mentioning
confidence: 99%
“…Youth) is a key transcription factor regulating pluripotency in mammalian early embryos and pluripotent stem cells. Cooperating with other master regulators of pluripotency, NANOG plays a central role in pluripotency (1)(2)(3) and forms autoregulatory loops to maintain ES cell (ESC) identity (4)(5)(6)(7). NANOG was initially identified from its ability to confer mouse (m)ESC selfrenewal without dependence on leukemia inhibitory factor (LIF) when overexpressed in mESCs (8,9).…”
mentioning
confidence: 99%